Numerische Modellierung und Simulation von bleifreien Relaxor-Ferroelektrikum-Kompositen - Streich, Friedemann (Schriftenreihe des Instituts für Angewandte Materialien, Karlsruher Institut für Technologie, 2023)
The electromechanical behavior of two new sodium bismuth titanate based lead-free ferroelectric materials as well as bilayer composites are investigated in experiments and numerical simulations. For the Finite-Element-Method, a fully coupled, three dimensional ferroelectric constitutive model is developed. In a parameter study, the electromechanical coupling of bilayer composite is optimized.